In the Footsteps of My Countrymen: Atmospheric Chemistry in New England, Los Angeles, and the Southeast United States. Issue 1 (21st December 2021) - de Gouw, Joost
Abstract: The formation of organic aerosol in the atmosphere degrades air quality and impacts climate change, but has been poorly understood for many years. This article gives a personal history of field studies that have advanced my scientific understanding. Measurements in New England in 2002, Los Angeles in 2010, and the Southeast U.S. in 2013 showed how organic aerosol is formed in these regions, which are distinctly different in their mixtures of natural and anthropogenic emissions. In taking this research path, I followed in the footsteps of two countrymen, Arie Haagen‐Smit and Frits Went, who did foundational work on air pollution in Los Angeles and haze formation from natural emissions. Plain Language Summary: Fine particles in the atmosphere are an important air pollutant as they can penetrate deep into the lungs of people. They also scatter sunlight, which makes the atmosphere look hazy and which has a cooling effect on climate. A large fraction of fine particles consists of organic molecules, but it has been a scientific challenge to find out where these come from. This article describes the results from field studies in New England, Los Angeles, and the Southeast U.S. These regions are very different in their emissions of organic compounds to the atmosphere: man‐made emissions are high in Los Angeles, while natural emissions from forests in the Southeast U.S. dominate over other sources. The contrast between the observations in the different regions gave insight into which organic molecules are chemically transformed and end up as fine particles in the atmosphere. Key Points: The formation of organic aerosol in the atmosphere degrades air quality and impacts climate change, but has been poorly understood for many years Field studies in New England, Los Angeles, and the Southeast U.S. showed that polluted air contains a much larger pool of organic aerosol precursors than previous measurements had uncovered, and how inorganic air pollutants can enhance the formation of organic aerosol Rapid developments in mass spectrometry have enabled the progress in our scientific understanding of organic chemistry in the atmosphere